Metamorphism and deformation associated with lower crustal pseudotachylytes in Southern Lofoten - Seabra Maronni, Natalia (2021)
Much debate is still happening on the subject of earthquakes in the lower crust. Pseudotachylytes are considered to be the only known evidence for such earthquakes in exhumed rocks (Steltenpohl et al., 2006). This thesis will investigate pseudotachylyte-bearing granulites from Lofoten, Norway. The three localities visited exhibit exhumed pristine pseudotachylytes in granulitic and retro-amphibolitic rocks: Hamnøya, Ølkonvatnet (on Moskenesøya) and Ramberg (on Flakstadøya). The samples used for this study were collected from these areas. The laboratory work consists of detailed mineralogical, microstructural, and geochemical characterization of host rocks, petrological modelling to constrain the pressure and temperature conditions during metamorphism, and mineralogical and microstructural characterization of pseudotachylytes. Microstructures in the host rock, such as corona rims, chemical zoning (complex feldspars), exsolution lamellae and symplectites, give information about metamorphic conditions, fluid-induced deformations and mineral reactions. Pseudotachylytes mineralogy reflects that of the host rocks, and microstructures within the veins indicate rapid cooling (i.e. cauliflower-shaped garnets, microlites and spherulites). P-T pseudosections suggest that the environment in which the pseudotachylytes formed is consistent with lower crust conditions (P = ∼7.2 to ∼9.8 Kbar and T = ∼880 to ∼1000 °C). The results yielded from these analysis led to the following conclusions: the rocks from each locality suffered fluid-induced reaction and deformation to different extents, suggesting that different volumes of free fluid were present in each locality; pristine pseudotachylytes show evidence of being rapidly crystallized from frictional melt of the host rocks, which was generated by seismic slip; the absence of ductile deformation in the nearly dry rocks suggests that high transient stress was necessary to trigger brittle deformation in the dry, strong granulitic lower crust.